"Like Kings in Their Kingdoms": Conservatism in Brazilian Psychoanalysis During the Dictatorship. Issue 4 (9th May 2017) - Frosh, Stephen; Mandelbaum, Belinda
Abstract : In this article, we examine some aspects of the fate of Brazilian psychoanalysis during the 1964–85 civil‐military dictatorship. Presenting data from interviews with Brazilian psychoanalysts and focusing on the activities of the Brazilian Psychoanalytic Society of São Paulo, we argue that the external political situation was paralleled by conservatism within the Society, with some dangerous consequences. We attend especially to tensions between right‐ and left‐wing psychoanalysts, denunciations and fear, and the impact of Bion's ideas. We conclude by suggesting that the "complicity" of the Society with the governing norms was coincident both with the self‐interests and attitudes of particular individuals and with normalizing institutional tendencies in psychoanalysis itself.